STRUCTURAL INSIGHTS FROM THE STUDY OF CS-EXCHANGED SMECTITES SUBMITTED TO WETTING-AND-DRYING CYCLES - Cuadros J. (My University, 2002)
Six smectites of different tetrahedral and octahedral compositions (SAz-1, Chambers, Belle Fourche, two subsamples of nontronite 33B and SWy-1) were Cs-exchanged and submitted to 70 wetting-and-drying cycles. X-ray diffraction (XRD) of oriented and glycolated mounts of the resultant material showed non-expandable layer proportions ranging from 15 to 60%. They were also analysed by powder XRD at 200°C in vacuum. These patterns showed that 15–40% of the layers were not rotated relative to each other and the rest were randomly rotated (no rotations of the 60° and 120° types).All layers had a d-spacing of 11 Å, corresponding to collapsed layers with Cs in the cavities created by the hexagonal rings of the tetrahedral sheets. Analysis of the number of cavities available in relation to the layer rotation shows that the rotation angle must be close to 30° or its multiples 90, 150, 210, 270 and 330°. X-ray diffraction and thermal analysis detected the same proportion of cis- and trans-vacant sites in the smectites. The ideal b dimensions of the tetrahedral and octahedral sheets (the sheets are considered independently, without deformation) were calculated for the samples used in this work and for others from the literature, using the tetrahedral and octahedral compositions. These ideal b dimensions have a strong positive correlation. The cis/trans- vacant character of the smectites is related to the relative lateral dimensions of the ideal tetrahedral and octahedral sheets. A possible explanation of this fact is offered, in which the different configurations of hydroxyls and oxide ions in cis- and trans-vacant structures can affect octahedral-sheet dimension.